Issues at the Rural-Urban Fringe: Florida's Agricultural Enclave Law - Rodney L. Clouser (EDIS)
FE560, a 4-page fact sheet by Rodney L. Clouser, describes changes to the Florida Agricultural Land and Practices Act, the definition agricultural enclaves, and implications of the act. Includes references. Published by the UF Department of Food and Resource Economics, October 2007.